KEDUDUKAN PANGLIMA LAOT LHOK DALAM KALANGAN MASYARAKAT NELAYAN (Studi Kasus Kecamatan Meureubo, Aceh Barat) - Rahmat Fithra (Prodi Ilmu Hukum, Universitas Teuku Umar, 2018)
Indonesia is an archipelagic country, two-thirds of Indonesia's territory is sea, so thus the potential of marine resources is abundant. Utilization and management of natural resources in the national interest is expected to provide an opportunity for all indigenous and tribal peoples to exercise the rights of the community. Indigenous and tribal peoples play an important role in managing, building and utilizing the environment. Customary institution in charge of fisheries and marine in Aceh is the customary institution Panglima Laot. Panglima Laot is divided into Panglima Laot Provinsi, Panglima Laot Regency / City, and Panglima Laot Lhok residing in sub district. Panglima Laot has a duty as mandated in Qanun No.10 of 2008 on Customary Institution that is, to carry out, maintain and supervise the implementation of customs and customary law, to assist the Government in the field of fisheries and marine, resolve disputes and disputes that occur among fishermen in accordance with customary law provisions laot, maintain and preserve the function of coastal and marine environment, fight for improving living standards of fishing communities, and prevent illegal fishing. But Panglima Laot Lhok Kecamatan Meureubo has not run smoothly as expected. Keywords : Customary law communities, fishermen, Panglima Laot Lhok.